WOMEN'S DAILY MOBILITY: CASE STUDY OF CONSTANTINE, ALGERIA - Nawel Achour-Bouakkaz; Ouafa Saighi; Asma Benbouhedja; Oulfa Nouha Kouri (International Journal of Innovative Technologies in Social Science, 2024)
Daily mobility is a crucial issue for women, shaping their access to opportunities and their experience of the city. This paper presents the preliminary results of a study on mobility of women who live and work in Constantine (Algeria). The aim is to provide answers to the following questions: What are the daily mobility patterns (analogies or differences) of women in this city? What types of mobility do women prefer, depending on where they live ? What difficulties and/or obstacles do women face in accessing urban space ? The adopted methodology is based on a questionnaire survey coupled with observations of the daily journeys of women between the domestic sphere and the urban space. The results showed how access to space is conditioned, managed and even governed by their displacement. Moving around becomes the first conscious act that connects them to space. And within this relationship to space, the notion of mobility is a strong link, one of the 'tools' linking them to the city. Moreover, the 'motor skills' available to the women in Constantine are experienced as both a mean and a constraint in everyday life. For some of them, it is an intermediary mean of accessing spaces both inside and outside the city. This study opens up avenues for research related to understanding urban dynamics and promoting inclusive planning.